Temperature and pressure effect on the anisotropy of dielectric permeability in KDP and DKDP crystals - Kedyulich, V.M.; Slivka, A.G.; Gerzanich, E.I.; Guivan, A.M.; Lukach, P.M. (Condensed Matter Physics, 2003)
Temperature dependences of longitudinal and transverse dielectric permeability
of KDP and DKDP crystals are studied at different values of hydrostatic
pressure in order to determine the pressure behaviour of the isotropic
point for these crystals. The isotropic point temperature in KDP crystals
at atmospheric pressure is Ti = 186 K at the measuring field frequency
1 kHz and Ti = 176 K at the frequency of 1 MHz. In DKDP crystals
the isotropic point is achieved at the temperature Ti = 300 K ( 1 kHz)
and Ti = 253 K ( 1 MHz). The hydrostatic pressure increase results in the
reduction of the isotropic point temperature with the pressure coefficients
∂Ti/∂p = −4.3 K/kbar for KDP and ∂Ti/∂p = −2.9 K/kbar for DKDP.
The analysis of the experimental results in the framework of the Blinc-Zeks
pseudospin formalism has shown a good agreement between the calculated
and the experimentally obtained temperature of the isotropic point for
KDP crystals. Проведено дослідження температурних залежностей повздовжньої
та поперечної діелектричної проникності кристалів KDP та DKDP
при різних величинах гідростатичного тиску з метою визначення
баричної поведінки температури ізотропної точки для цих кристалів. Температура ізотропної точки в кристалах KDP при атмосферному тиску становить Ti = 186 K при частоті вимірювального поля 1 кГц та Ti = 176 K на частоті 1 МГц. В кристалах DKDP ізотропна точка реалізується при температурах Ti = 300 K (1 кГц) та
Ti = 253 K ( 1 МГц). Збільшення гідростатичного тиску приводить
до пониження температури ізотропної точки з баричними коефіцієнтами ∂Ti/∂p = −4.3 К/кбар для KDP та ∂Ti/∂p = −2.9 К/кбар для
DKDP. Аналіз експериментальних результатів в рамках псевдоспінового формалізму Блінца-Жекша показав, що існує добре узгодження між розрахованою та експериментально визначеною температурою ізотропної точки для кристалів KDP.